Improving children's performance on photographic line-ups: do the physical properties of a ‘wildcard’ make a difference? - Zajac, Rachel (Legal and criminological psychology, 2016)
Purpose. Children's performance on target-absent photographic line-ups may improve when they have the option of pointing to a wildcard – a photo of a silhouetted figure with a question mark superimposed. We investigated whether the wildcard's physical properties influence its success. Methods. Children (7–11 years, N = 237) briefly saw one of two confederates during a staged event; 1–2 days later, they completed either a target-present or target-absent line-up task. Within each condition, children either saw a wildcard with a plausible silhouette (i.e., consistent with the silhouette of the target), a wildcard with an implausible silhouette (i.e., inconsistent with the silhouette of the target), a wildcard with no silhouette (i.e., a question mark only), or no wildcard. Results. Wildcard condition did not influence children's target-present performance. On target-absent line-ups only the plausible wildcard increased children's accuracy above that of children in the no wildcard control condition. Conclusions. The wildcard may only be successful to the extent that its silhouette is a plausible representation of the target. Possible explanations for this outcome and implications for using wildcards in investigative practice are discussed.